Anxiety Sensitivity Prospectively Predicts Increased Acute Posttraumatic Stress and Related Symptoms After Sexual Assault. Issue 6 (11th November 2020) - Short, Nicole A.; Lechner, Megan; Bell, Kathy; Black, Jenny; Buchanan, Jennie; Ho, Jeffrey; Reed, Gordon; Corzine, Amanda; Riviello, Ralph; Martin, Sandra L.; Liberzon, Israel; Rauch, Sheila; et al.
Abstract: Anxiety sensitivity is a potential risk factor for posttraumatic stress symptoms (PTSS) and has been hypothesized to contribute to PTSS development. However, few prospective studies have evaluated whether anxiety sensitivity predicts PTSS. In a subsample of 48 women sexual assault survivors enrolled as part of a larger prospective observational study, elevated anxiety sensitivity measured via a brief assessment 1 week after experiencing a sexual assault was concurrently associated with PTSS at 1 week and prospectively predicted PTSS 6 weeks after the event, with small‐to‐medium effect sizes, η 2 p = .10, even after covarying for trauma history. Heightened anxiety sensitivity at 1‐week postevent also interacted with time to predict anxiety and depression both before and after sexual assault, with medium‐to‐large effect sizes, ηp 2 = .21– .24. This is consistent with research linking anxiety sensitivity to PTSS, but this was the first prospective study of which we are aware to demonstrate that anxiety sensitivity in the acute posttrauma period predicts PTSS among women who have recently experienced sexual assault. Future research should use the full Anxiety Sensitivity Index to replicate findings in a larger sample and explore whether targeting anxiety sensitivity could mitigate the development of PTSS in this vulnerable population. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) La sensibilidad a la ansiedad predice prospectivamente un aumento del estrés postraumático agudo y síntomas relacionados después de una agresión sexual SENSIBILIDAD A LA ANSIEDAD Y TEPT DESPUÉS DE UNA AGRESIÓN SEXUAL La sensibilidad a la ansiedad es un factor de riesgo potencial para los síntomas de estrés postraumático (SEPT) y se ha planteado la hipótesis de que contribuye al desarrollo de SEPT. Sin embargo, pocos estudios prospectivos han evaluado si la sensibilidad a la ansiedad predice el TEPT. En una submuestra de 48 mujeres sobrevivientes de agresión sexual inscritas como parte de un estudio observacional prospectivo más grande, la sensibilidad a la ansiedad elevada, medida a través de una breve evaluación 1 semana después de experimentar una agresión sexual, se asoció simultáneamente con los SEPT a la semana 1 y los SEPT predicho prospectivamente 6 semanas después de la agresión sexual, con tamaños de efecto pequeños a medianos, η2 p = .10, incluso después de covariar por antecedentes de trauma. La mayor sensibilidad a la ansiedad una semana después del evento también interactuó con el tiempo para predecir la ansiedad y la depresión antes y después de la agresión sexual, con tamaños de efecto de medianos a grandes, ηp 2 = .21– .24. Esto es consistente con la investigación que relaciona la sensibilidad a la ansiedad con los SEPT, pero este fue el primer estudio prospectivo del que sabemos que demuestra que la sensibilidad a la ansiedad en el período postraumático agudo predice los SEPT entre las mujeres que han experimentado recientemente una agresión sexual. Futuras investigaciones deberían utilizar el Índice de Sensibilidad a la Ansiedad completo para replicar los hallazgos en una muestra más grande y explorar si la sensibilidad a la ansiedad podría mitigar el desarrollo de SEPT en esta población vulnerable. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐20‐0044.R3 Lechner Anxiety sensitivity prospectively predicts increased acute posttraumatic stress and related symptoms after sexual assault Traditional Chinese 標題: 焦慮敏感性能前瞻性地預測受性侵犯後, 急性創傷後壓力提升和相關症狀 撮要: 焦慮敏感性是創傷後壓力症狀 (PTSS) 的潛在風險因素, 並被假設會促成PTSS的發展。然而, 少有前瞻性研究評估焦慮敏感性能否預測PTSS。我們以參與一個更大的前瞻性觀察研究當中的子樣本, 即48名性侵犯倖存女性為本研究的樣本。經歷性侵犯後一週後的焦慮敏感性提高, 跟一週後的PTSS有同時關係, 並前瞻性地預測事發六週後的PTSS, 效應量為小至中等, η 2 p = .10, 即使考慮了創傷史共變後亦然。事發一週後的焦慮敏感度提升也與時間互動, 預測了性侵犯前與後的焦慮症和抑鬱症, 效應量為中至大, η 2 p = .21‐ −24。這個發現, 跟將焦慮敏感性與PTSS連繫起來的研究結果是一致的, 但這是我們所知首個前瞻性研究, 證明在近期曾經歷性侵犯的女性當中, 焦慮敏感性在創傷後的危急期能預測PTSS。未來研究應使用完整的焦慮敏感性指標, 及分析更大的樣本以重複驗證結果, 並探索針對治療焦慮敏感性, 可否緩和這類脆弱人口中PTSS的發展。 Simplified Chinese 标题: 焦虑敏感性能前瞻性地预测受性侵犯后, 急性创伤后压力提升和相关症状 撮要: 焦虑敏感性是创伤后压力症状 (PTSS) 的潜在风险因素, 并被假设会促成PTSS的发展。然而, 少有前瞻性研究评估焦虑敏感性能否预测PTSS。我们以参与一个更大的前瞻性观察研究当中的子样本, 即48名性侵犯幸存女性为本研究的样本。经历性侵犯后一周后的焦虑敏感性提高, 跟一周后的PTSS有同时关系, 并前瞻性地预测事发六周后的PTSS, 效应量为小至中等, η 2 p = .10, 即使考虑了创伤史共变后亦然。事发一周后的焦虑敏感度提升也与时间互动, 预测了性侵犯前与后的焦虑症和抑郁症, 效应量为中至大, η 2 p = .21‐ −24。这个发现, 跟将焦虑敏感性与PTSS连系起来的研究结果是一致的, 但这是我们所知首个前瞻性研究, 证明在近期曾经历性侵犯的女性当中, 焦虑敏感性在创伤后的危急期能预测PTSS。未来研究应使用完整的焦虑敏感性指标, 及分析更大的样本以重复验证结果, 并探索针对治疗焦虑敏感性, 可否缓和这类脆弱人口中PTSS的发展。